A simplified PWM technique for PV fed Five-Level Five switch Multilevel Inverter - Algburi, Ali Qasim Hussein; Rao, P. V. Ramana (International Journal of Engineering and Technology, 2018)
Bulk electrical power generation is generated using fossil fuels which emit huge pollution which is a global constraint today. Non-conventional sources of energy are the alternative energy sources for power generation. Non-conventional sources like PV (photo-voltaic) system are used as power source now-a-days. Multi-level inverters (MLI) are dominating inverter circuits giving out voltage with less distortion eventually reducing voltage stress on switches and size of filter. This paper presents a MLI structure with five switches giving out five-level output from the inverter. PV system is used as source and boost converter amplifies the PV output voltage to desired value. The paper presents a simplified PWM (pulse width modulation) technique for PV fed five switch five-level inverter. The proposed system is developed and results are obtained using MATLAB/SIMULINK software. Results are presented for the system considering R-load and RL-load conditions.